Analysis of complete mitochondrial genome of Etisus anaglyptus (Arthropoda, Decapoda, Xanthidae) with phylogenetic consideration - Mustafa Zafer Karagozlu; Thinh Do Dinh; Van Quan Nguyen; Chang-Bae Kim (Mitochondrial DNA. Part B. Resources, 2018)
The complete mitochondrial genome is sequenced and analyzed from a xanthid crab Etisus anaglyptus, which is the first complete mitochondrial genome for the genus. The mitochondrial genome length of E. anaglyptus is 16,435 bp and it is composed of 13 protein coding genes, two ribosomal RNA genes, and 22 tRNA genes. The structure and gene orientation of the mitochondrial genome is identical with the other brachyuran records. Furthermore, phylogenetic relationships of the infraorder Brachyura evaluated by mitochondrial protein coding genes. The phylogenetic study showed that E. anaglyptus is positioned in the superfamily Xanthoidea and the closest species to E. anaglyptus is Leptodius sanguineus.